2011
DOI: 10.1103/physrevb.84.233406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of potassium doping on electrical properties of carbon nanotube fibers

Abstract: We investigate the effect of potassium (K) doping on the transport properties of aligned single-walled carbon nanotube fibers. The temperature dependence of the electrical resistance, the current-voltage characteristics, and the magnetoresistance vs external magnetic field of the fibers consistently show that doping enhances the metallic character of the fibers and that the response of the samples can be quantitatively explained in two thermal regimes separated by a characteristic temperature T * . At temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 19 publications
1
34
0
3
Order By: Relevance
“…So far, various studies have shown an excellent fit between Equation and the experimentally measured temperature dependence . The validity for CNT thin films was found in a much broad temperature range of 12–300 K .…”
Section: Structure and Fundamental Propertiesmentioning
confidence: 74%
See 1 more Smart Citation
“…So far, various studies have shown an excellent fit between Equation and the experimentally measured temperature dependence . The validity for CNT thin films was found in a much broad temperature range of 12–300 K .…”
Section: Structure and Fundamental Propertiesmentioning
confidence: 74%
“…The electron transport in CNT fibers, and more generally in CNT assemblies, is different from that in individual nanotubes. To understand the mechanism of electronic transport, there have been intensive investigations . According to the studies on the temperature, electric field, and magnetic field dependent electrical conductivity of CNT networks, 3D variable range hopping (VRH) is responsible for the electrical charge transport.…”
Section: Structure and Fundamental Propertiesmentioning
confidence: 99%
“…Also shown is the normalized resistance of the bare fiber before the Ni electrodeposition which indicates its semiconducting character in the whole temperature range investigated. This effect has been previously studied 16 and a three-dimensional variable range hopping (VRH) regime 5 has been evidenced with a R vs T dependence well fitted by the expression R = R N e (T M /T ) 1/4 in the temperature range 3-50 K. Depositing Ni nanoparticles on the fiber surface generates an enhancement of their metallic properties. For short deposition times the fibers are still semiconducting with a negative slope in the R vs T curve.…”
Section: Samples Fabrication and Characterizationmentioning
confidence: 81%
“…On the other hand, many studies (for instance [13]) have shown that all the electrical and magnetic characteristics of the CNTs are changeable via doping procedure and theoretically it would be possible by doping alkali metals in the s-CNTs their semiconducting and also their photoconducting properties to be regulated for empirical applications (because doping of the alkali metals increase electron density in the conduction band of the doped CNTs). Salvato et al (2011) [14] have investigated the effect of potassium doping on the transport properties of aligned single-walled CNT fibers. They found that the I-V (current-voltage) characteristics and the magnetoresistance of the fibers consistently show that doping enhances the metallic character of the fibers and at higher than a characteristic temperature; enhancement in the K-doped sample is due to the increase of the density of states, which raises carrier's hopping.…”
Section: Introductionmentioning
confidence: 99%